2015
DOI: 10.3389/fnins.2015.00475
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-Concentrating Hormone (MCH): Role in REM Sleep and Depression

Abstract: The melanin-concentrating hormone (MCH) is a peptidergic neuromodulator synthesized by neurons of the lateral sector of the posterior hypothalamus and zona incerta. MCHergic neurons project throughout the central nervous system, including areas such as the dorsal (DR) and median (MR) raphe nuclei, which are involved in the control of sleep and mood. Major Depression (MD) is a prevalent psychiatric disease diagnosed on the basis of symptomatic criteria such as sadness or melancholia, guilt, irritability, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 136 publications
(193 reference statements)
1
35
0
Order By: Relevance
“…In addition to this, peptide E.IGDEENSAKFPI(‐.98).G derived from Pro‐MCH precursor was also downregulated −48% ( p = 0.037) in the PFC region. It has been reported that the neuropeptide MCH plays a role in rapid eye movement (REM) sleep and is involved in the pathophysiology of depression . Some authors have demonstrated that MCH receptor‐1 antagonist (SNAP‐7941) possesses antidepressant and anxiolytic effects in animal models of depressive disorder .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, peptide E.IGDEENSAKFPI(‐.98).G derived from Pro‐MCH precursor was also downregulated −48% ( p = 0.037) in the PFC region. It has been reported that the neuropeptide MCH plays a role in rapid eye movement (REM) sleep and is involved in the pathophysiology of depression . Some authors have demonstrated that MCH receptor‐1 antagonist (SNAP‐7941) possesses antidepressant and anxiolytic effects in animal models of depressive disorder .…”
Section: Resultsmentioning
confidence: 99%
“…Areas linked to reward are innervated by MCH/NEI neurons, including light innervation of the caudate‐putamen and moderate innervation of the ventral tegmental area, with MCH/NEI‐ir fibers contacting dopaminergic neurons in the latter, supporting the circuit suggested by Domingos et al (). Actions of MCH on learning, memory consolidation/retrieval, and emotion (Le Barillier et al, ; Monzon et al, ; Sita et al, ; Torterolo et al, ) also had a clear anatomical substrate in M musculus mice, with a dense innervation of the medial septal nucleus and the dorsal part of the hippocampal formation, similar to Rattus (Lima et al, ). Similar observations were made for autonomic modulation mediated by the nucleus of the solitary tract and the PVH (Abbott et al, ; Brown, Chitravanshi, Kawabe, & Sapru, ), sleep and arousal mediated by the dorsal raphe and the ventrolateral periaqueductal gray matter (Clément et al, ; Lagos et al, ; Lagos, Torterolo, Jantos, & Monti, ), and sensory integration through projections to olfactory areas and the medial septal nucleus (Adams et al, ; Miller et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ior (Bouret, Draper, & Simerly, 2004;Stanley & Leibowitz, 1985;Stratford & Kelley, 1997), and injections of MCH or MCHR1 antagonist in these areas have been shown to modulate ingestion (Abbott et al, 2003;Georgescu, Sears, & Hommel, 2005 (Segal-Lieberman et al, 2003) and the animal emotional state (Borowsky et al, 2002). Emotional state and sleep may also be regulated through the dorsal and median raphe nuclei (Monti, Pandi-Perumal, & Torterolo, 2018;Torterolo et al, 2015;Urbanavicius, Lagos, López, Torterolo, & Scorza, 2018). The high density of MCHR1 in the caudate-putamen and its presence in the ventral tegmental area also allows MCH to act on reward circuits through the mesolimbic pathway (Domingos et al, 2013).…”
Section: F I G U R Ementioning
confidence: 99%